Changes on organic acid secretion and accumulation in Plantago almogravensis Franco and Plantago algarbiensis Samp. under aluminum stress - Martins, Neusa (2013)
We investigated the effect of Al (400 M) on organic acids secretion, accumulation and metabolism in Plantago almogravensis Franco and Plantago algarbiensis Samp. Al induced a significant reduction on root elongation only in P. algarbiensis. Both species accumulated considerable amounts of Al(>120 g g−1) in their tissues, roots exhibiting the highest contents (>900 g g−1). Al stimulated malonic acid secretion in P. algarbiensis, while citric, succinic and malic acids were secreted by P. almogravensis. Moreover, Al uptake was accompanied by substantial increases of citric, oxalic, malonic and fumaric acids contents in the plantlets of either species. Overall, the acid metabolizing enzymes were not directly involved in the Al induced organic acid secretion and accumulation. Our data suggest that Al detoxification in P. almogravensis implies both secretion of organic acids from roots and tolerance to high Al tissue concentrations, while in P. algarbiensis only the tolerance mechanism seems to be involved.